Emerging Educational Design in Online Training in Higher Education - Silva-Quiroz, J (SCIENTIA SOCIALIS, 2021)
Universities are living in a time of major transitions regarding the challenge of rethinking and transforming the current pedagogical models so they can respond to the needs of the global knowmad society. In this study, the Design-Based Research (DBR) approach is used to address the improvements of two emerging pedagogical designs in e-learning in the university context: the model of the Center for Research in Education and ICT (CIIET) of the University of Santiago de Chile (Chile) and the model developed by the Education Node research group of University of Extremadura (Spain). The main focus of these models is the student, who by developing activities based on the resolution of a contextualized problem and using new strategies, accompanied by open resources for resolution, resulting in a learning outcome that can be achieved and measured through assessment. This work aims to advance in identifying of some pedagogical keys for the design of online training scenarios that promote environments of production, research, and open dissemination of best practices, to experience new creative forms and collaborative learning, which have emerged within the hyper connected society and the net-culture.